2014
DOI: 10.1017/s1461145714000248
|View full text |Cite
|
Sign up to set email alerts
|

Repeated treatment with electroconvulsive seizures induces HDAC2 expression and down-regulation of NMDA receptor-related genes through histone deacetylation in the rat frontal cortex

Abstract: The enzymatic activity of histone deacetylases (HDACs) leads to a histone deacetylation-mediated condensed chromatic structure, resulting in transcriptional repression, which has been implicated in the modifications of neural circuits and behaviors. Repeated treatment with electroconvulsive seizure (ECS) induces changes in histone acetylation, expression of various genes, and intrabrain cellular changes, including neurogenesis. In this study, we examined the effects of repeated ECS on the expression of class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 78 publications
2
27
0
1
Order By: Relevance
“…Indeed, it has been found that Hdac2 mRNA and protein levels increase after chronic ECS whereas acute ECS causes a non-significant upregulation (Park et al, 2014). Following chronic ECS, HDAC2 occupancy increased at the promoters of c-Fos and Egr1 with corresponding reductions in histone acetylation of H3 and/or H4 proteins (Park et al, 2014). This was correlated with decreased gene expression, which interestingly was ameliorated by the administration of sodium butyrate, a HDAC inhibitor, during the course of ECS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been found that Hdac2 mRNA and protein levels increase after chronic ECS whereas acute ECS causes a non-significant upregulation (Park et al, 2014). Following chronic ECS, HDAC2 occupancy increased at the promoters of c-Fos and Egr1 with corresponding reductions in histone acetylation of H3 and/or H4 proteins (Park et al, 2014). This was correlated with decreased gene expression, which interestingly was ameliorated by the administration of sodium butyrate, a HDAC inhibitor, during the course of ECS.…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation is that the post-ECS Arc repression results from histone modifications. Indeed, it has been found that Hdac2 mRNA and protein levels increase after chronic ECS whereas acute ECS causes a non-significant upregulation (Park et al, 2014). Following chronic ECS, HDAC2 occupancy increased at the promoters of c-Fos and Egr1 with corresponding reductions in histone acetylation of H3 and/or H4 proteins (Park et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that the functional difference between the left and right HPCs affected our results, as shown by the laterality of NMDA receptor distribution in the HPCs in a previous study (Goto et al, 2010). Since ECT is suggested to alter NMDA receptor (Park et al, 2014) and glutamate/glutamine expression levels (Michael et al, 2003), the asymmetric effects of ECT on neuronal HPC circuits associated with NMDA might occur after ECT. Further studies to reveal the pathophysiological mechanisms underlying the long-term effects of ECT on brain function are neces- There were several limitations in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Other studies have reported PTM of histone variants following seizures in relation to DNA damage (Crowe et al 2011). Expression of HDAC2 is up-regulated in experimental and human epilepsy (Huang et al 2002(Huang et al , 2012, and predicted effects of changes in HDAC activity include transcriptional responses for several genes implicated in synaptic function, including ionotropic and metabotropic glutamate receptors (Huang et al 1999;Kurita et al 2012;Park et al 2014).…”
Section: Histone Modifications and Epilepsymentioning
confidence: 98%